EFFECTS OF CALCIUM OIL IN COMMERCIAL DIETS ON EIGHT AND ABDOMEN BROILER FAT - I M., Andi; Suasta, I M.; Bidura, I G. N. G. (Jurnal Peternakan Tropika, 2020)
This research aims to determine the effects of calcium oil in commercial diets to broiler pads fat, mesentery fat, and ventricular fat. This research has been conducted for 35 days in Faculty of Animal Husbandry Farm, Located at Bukit Jimbaran, Bali. This Research used completely randomized design (RAL) with 4 treatments and 6 replications. Each plot was filled with 5 chicks 7 day of age with homogeneous body weight. The four treatments were broiler that were diets without calcium oil as a control (A), commercial diets with 1% of calcium oil (B), commercial diets with 2% of calcium oil (C), and commercial diets with 3% of calcium oil (D). The observed variables were weight, pads fat, mesentery fat, and ventricular fat. The results showed that 1-3% calcium oil in commercial diets, the weight of treatment B was not significantly different (P>0.05)  and treatment C and D were significantly lower (P>0.05) compared with treatment A.  Pads fat on treatment B, C, and D were significantly (P<0.05) lower than treatment A while mesentery fat and ventricular fat were not significantly different (P> 0.05).  From the results this research it can be concluded that 1-3% oil in commercial  can reduce broiler abdominal fat.   Keywords: Broiler, Calcium Oil, Pad fat